Strategy of the Amil Zakat Infaq and Sedekah Mitra Ummat Madani Institutions in Implementing the Program of Education - Sarah, May; Irwandi, Irwandi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2023)
The main problem in this study is regarding the various obstacles to education for the poor, based on social facts through interviews and phenomena encountered in the Padang city community, one of the roots of the education problem lies in the weak community economy so that many dhuafa children are constrained in privately based schools. The educational constraints that often occur among the poor are school debt from tuition/UKT payments, school exam payments, development payments and so on, so that they cannot get a diploma to apply for jobs and continue their education to a higher level. This study aims to find out the strategies of the amil zakat infaq and sedekah Mitra Ummat Madani institutions in implementing educational programs to help the education of the dhuafa, and then find out what are the drivers and obstacles of Lazis Mitra Ummat Madani in delivering educational programs to the dhuafa in Padang City. The type of research that the authors use is a type of field research (Field Research), to obtain data from the problems studied. The data collection technique that the writer uses is through interviews and documentation. Data management was carried out in a qualitative descriptive manner, then described and classified aspects of certain problems and explained through effective sentences. The lack of attention in the field of education for dhuafa (non-orphanage) children has led Lazis Mitra Ummat Madani to create an educational program with another name, namely the civil generation scholarship program (Pro Be GEMA). Supporting factors in channeling the program by making donors as foster parents for orphans and dhuafa in terms of supporting their education so that the education of orphans and dhuafa is given more attention. There are 3 taglines for the Madani Generation Scholarship Program, namely fostering generations of Qur'an memorizers by establishing tahfiz houses, having noble character through various kinds of religious activities and achieving achievements in the formal and informal fields.